2021
DOI: 10.1111/ppl.13366
|View full text |Cite
|
Sign up to set email alerts
|

An isopentenyl transferase transgenic wheat isoline exhibits less seminal root growth impairment and a differential metabolite profile under Cd stress

Abstract: Cadmium is one of the most important contaminants and it induces severe plant growth restriction. In this study, we analyzed the metabolic changes associated with root growth restriction caused by cadmium in the early seminal root apex of wheat. Our study included two genotypes: the commercial variety ProINTA Federal (WT) and the PSARK::IPT (IPT) line which exhibit high‐grade yield performance under water deficit. Root tips of seedlings grown for 72 h without or with 10 μM CdCl2 (Cd‐WT and Cd‐IPT) were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Isopentenyltransferases are of particular importance for plant metal stress responses as their overexpression can result in improved heavy metal stress tolerance (Gomez Mansur et al, 2021; Thomas et al, 2005). Accordingly, IPT ‐induced CTKs in transgenic tobacco enhanced copper stress tolerance, and this was explained by an increased expression of a metallothionein‐like gene (Thomas et al, 2005).…”
Section: A Path Towards Better‐engineered Iptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isopentenyltransferases are of particular importance for plant metal stress responses as their overexpression can result in improved heavy metal stress tolerance (Gomez Mansur et al, 2021; Thomas et al, 2005). Accordingly, IPT ‐induced CTKs in transgenic tobacco enhanced copper stress tolerance, and this was explained by an increased expression of a metallothionein‐like gene (Thomas et al, 2005).…”
Section: A Path Towards Better‐engineered Iptsmentioning
confidence: 99%
“…Accordingly, IPT ‐induced CTKs in transgenic tobacco enhanced copper stress tolerance, and this was explained by an increased expression of a metallothionein‐like gene (Thomas et al, 2005). Likewise, a transgenic wheat line, overexpressing IPT under the SARK::IPT promoter, showed a lower reduction in root growth under cadmium stress, and this was attributed to the activation of phenolic secondary metabolism, increased antioxidant defences, and cell wall reinforcement (Gomez Mansur et al, 2021). Another study, using Arabidopsis, reported an opposite relationship whereby, CTK depletion plants ( ipt1,3,5,7 loss of function) gained selenium tolerance through the induced antioxidant enzyme activities and increased glutathione (GSH) content (Jiang et al, 2019).…”
Section: A Path Towards Better‐engineered Iptsmentioning
confidence: 99%
“…The TaEXPB8 gene can increase antioxidant defence by stimulating the secondary metabolism of phenols, having positive effects on cell wall strengthening at the same time. This enables the plant to respond to cadmium toxicity (Gomez Mansur et al 2021). In addition, expansins play crucial roles in plants under low-temperature stress.…”
Section: Introductionmentioning
confidence: 99%